The Potential Of Palm Waste Biochar For Slow Release Fertilizer - Hendrix Yulis Setyawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2022)
Charcoal-based fertilizers can be improved in quality by nutrient impregnation and modified to provide nutrients gradually (slow release fertilizer-SRF). SRF fertilizer can be made by using a coating in the form of charcoal from the pyrolysis of palm oil waste. Raw palm oil waste from Bantur District, Malang, East Java, for the soaking process with fertilizers, there are two different types of fertilizers, namely organic (EM4) and inorganic (Urea) fertilizers, after which they are pyrolyzed and the characteristic results are obtained. Based on the research results, waste oil palm has the potential to be developed into a Slow Release Fertilizer. The content of water, ash, and volatile matter was found in the fertilizer which was soaked for 72 hours (3 days), while the bound carbon content was found in the soaking for 72 hours (3 days).